The export of sanction policies: Extraterritorial sanctions and geopolitical conflict - Eckhard Janeba (EconPol Forum, 2023)
The geopolitical rivalry between the US and China may spill over to Europe via extraterritorial sanctions. The US-Iran conflict shows that Europe losing access to the US market has been a powerful threat to limit Europe's trade with Iran. US extraterritorial sanctions, seen as a tool to limit Iran's sponsorship of international terrorism, became more attractive as the US became a energy exporter. Countermeasures against extraterritorial sanctions exist but proved largely ineffective in the past. European countries need to invest in strategic sovereignty to prepare for a possible fallout from the US-China geopolitical conflict.
Keywords: 330